Total hemoglobin mass - A new parameter to detect blood doping? - Prommer, N.; Sottas, P.-E.; Schoch, C.; Schumacher, Y. O.; Schmidt, W. (Medicine & Science in Sports & Exercise, 2008)
Purpose: All kinds of blood manipulations aim to increase the total hemoglobin mass (tHb-mass). To establish tHb-mass as an effective screening parameter for detecting blood doping, the knowledge of its normal variation over time is necessary. The aim of the present study, therefore, was to determine the intraindividual variance of tHb-mass in elite athletes during a training year emphasizing off, training, and race seasons at sea level.